Detection of nitrate and nitrite in different seafood. (1st August 2019) - Chiesa, Luca; Arioli, Francesco; Pavlovic, Radmila; Villa, Roberto; Panseri, Sara
Highlights: A method for NO2 − and NO3 − determination in seafood based on ion chromatography with suppressed conductivity was set-up. High resolution mass spectrometry is used as a confirmatory detection tool for revealing NO2 − and NO3 − ultra-trace levels. Significant differences in NO3 − levels between farmed and wild seafood species were found. The highest concentration of NO3 − was found in smoked salmon samples. NO2 − was not detected in any sample studied. Abstract: High-performance ion-exchange chromatography with suppressed conductivity (HPIEC-SCD) was validated for the determination of nitrite (NO2 − ) and nitrate (NO3 − ) in the edible part of diverse seafood species. Samples analyzed by HPIEC-SCD that were devoid of nitrite and nitrate were subjected to HRMS using a Q-exactive Orbitrap platform. As NO2 − is not detectable in Q-Exactive Orbitrap, it was necessary to perform the oxidation of NO2 − to NO3 − . Accordingly, suitability of NO2 − oxidation by H2 O2 as a part of sample preparation for HPIEC-HRMS was elaborated. The difference in the concentration of NO3 − before and after H2 O2 treatment was used for the evaluation of eventual NO2 − presence. The edible part of 53 fish, shrimp and bivalve species presented significant differences in NO3 − levels especially between farmed (median = 44 μg/g) and wild species (median = 16 μg/g). The highest concentration of NO3 − was found in smoked salmon samples (median = 60 μg/g) while NO2 − was not revealed in any of the samples studied.